Methodological Comparison of the Production Approach 2013 and 2019 for Quantifying the Carbon Stock in Harvested Wood Products in China - Yu, Zhihan; Zhang, Han; Tu, Qingshi; Yang, Hongqiang (Frontiers in Environmental Science, 2022)
Harvested wood products (HWP) play an important role in global climate change mitigation. The Production Approach, an internationally accepted HWP carbon accounting approach by the Intergovernmental Panel on Climate Change (IPCC), has been revised several times to enhance the accuracy of the accounting results. This study compared the methodological differences in the Production Approach elaborated in the 2013 Revised Supplementary Methods and Good Practice Guidance Arising from the Kyoto Protocol (PA2013) and 2019 Refinement to the 2006 IPCC Guidelines for National Greenhouse Gas Inventories (PA2019). We used PA2019 to calculate the HWP carbon stock in China under different wood utilization scenarios. In terms of recycling and reusing of recovered paper, we found that PA2019 has a more accurate representation of the increasing proportion of paper and paperboard materials produced using recovered paper in the world. In 2019, the HWP carbon stock in China was 815.94 Mt (1 Mt = 106 t) using PA2019. In detail, the carbon stock of sawnwood, wood-based panels, and paper and paperboard were 208.52 Mt, 559.73 Mt, and 47.69 Mt, respectively. Scenario simulation results show that half-life was an important factor that affecting HWP carbon stock. China can improve HWP carbon stock by increasing the recovered paper utilization rate for paper products or increasing the utilization rate of HWP with long half-life in construction (structural material). The additional carbon stock obtained by changing the utilization structure of wood and improve the half-life of HWP will not be large until decades later but nonetheless important.